2007
DOI: 10.1158/1535-7163.mct-06-0727
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of cyclin B1 sensitizes prostate cancer cells to apoptosis induced by chemotherapy

Abstract: Chemotherapeutic drugs ideally should take advantage of the differences between transformed and normal cells and induce apoptosis only in cancer cells. One such difference may be the overexpression of cyclin B1 protein in cancer cells, which is required for the proper progression through mitosis. Previously, we showed that treatment of human prostate cancer cells with 2-methoxyestradiol (2-ME) or docetaxel results in an accumulation of cyclin B1 protein and an increase in cyclin B1 kinase activity, followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 52 publications
5
47
0
Order By: Relevance
“…However, strong overexpression of the SmActin1, SmCyclinB, SmCaspase3 or SmCaspase7 genes from the SmActin1 promoter, induced mortality in schistosomula. This correlates with what is generally reported in other systems [40], [48]–[55], [63], although in some cases, gene overexpression causes morphological and developmental changes, as observed in human myoblast cells and esophageal squamous cell carcinoma [39], [40], [42]. The overexpression of each of these genes in schistosomula may alter schistosome early development and be the primary cause of the schistosome lethality observed.…”
Section: Discussionsupporting
confidence: 88%
“…However, strong overexpression of the SmActin1, SmCyclinB, SmCaspase3 or SmCaspase7 genes from the SmActin1 promoter, induced mortality in schistosomula. This correlates with what is generally reported in other systems [40], [48]–[55], [63], although in some cases, gene overexpression causes morphological and developmental changes, as observed in human myoblast cells and esophageal squamous cell carcinoma [39], [40], [42]. The overexpression of each of these genes in schistosomula may alter schistosome early development and be the primary cause of the schistosome lethality observed.…”
Section: Discussionsupporting
confidence: 88%
“…The AR has been reported to regulate cellular proliferation by control of CDK and cyclins at the transcriptional level and by posttranslational modifi cations that infl uence cell cycle protein activity, including overexpression of cyclin B in recurrent tumours [ 14 ] . A further facet of cyclin B overexpression has been reported, namely, to sensitize malignant prostate cells to apoptosis induced by chemotherapy [ 15 ] . BFGF has been reported to have several functions in advanced PCa.…”
Section: O L E C U L a R P H E N O T Y P I N G O F T U M O U R C E mentioning
confidence: 99%
“…Also our findings add to recent data suggesting that in CaP, tumor-associated hypoxia associates to malignant progression, metastasis, resistance to Figure 3A) were associated with Gleason score and disease prognosis ( Figure 3B). Since the products of CCNB1 (Gomez, de Las Pozas et al 2007) and HMMR (Gust, Hofer et al 2009) genes have been recently identified as molecular markers of CaP progression, our results suggest the potential utility of hypoxia-associated genes as a criterion to identify CaP biomarkers with prognostic value. In additional studies we found a high correlation between DLG7 and DNA topoisomerase 2α (TOP2A) transcript levels (Pearson Coefficient= 0.816) ( Figure 3C (Koffa, Casanova et al 2006).…”
Section: Figure 2 Different Gene Expression By Cap Cells In Hypoxia mentioning
confidence: 64%
“…Since the products of CCNB1 (Gomez, de Las Pozas et al 2007) and HMMR (Gust, Hofer et al 2009) genes have been recently identified as molecular markers of CaP progression, our results suggest the potential utility of hypoxia-associated genes as a criterion to identify CaP biomarkers with prognostic value. In additional studies we found a high correlation between DLG7 and DNA topoisomerase 2α (TOP2A) transcript levels (Pearson Coefficient= 0.816) ( Figure 3C).…”
Section: Figure 3 Three Hypoxia-controlled Genes Are Associated Witmentioning
confidence: 64%